Les formes de travail scientifique en STAPS : entre disciplinarité et interdisciplinarité - Collinet, C.; Terral, P.; Trabal, P. (Movement & Sport Sciences - Science & Motricité, 2016)
The STAPS follow a vast movement which is both political and scientific, and which encourages interdisciplinarity. Considered as able to produce specific but also heuristic knowledge in order to answer complex social questions, its implementation can be problematic for the usual scientific work. This discipline, originally pluridisciplinary, is fully related to interdisciplinarity. Based on a group of various texts and interviews with teachers-researchers, our study aims to a better understanding of the conditions of interdisciplinary activity. We underline tension, and sometimes contradictions between two injunctions related to interdisciplinary work: interdisciplinarity and academic disciplinary needs. We show that it is through six different types of work which we introduce as paths, understood as stabilized action regimes, that ways of interdisciplinary work in the field of STAPS can be observed.